Tendon Graft and Platelet Concentrate for Chronic Achilles Tendon Rupture. A Case Report - Yovanny Ferrer Lozano; Pablo Oquendo Vázquez; Yanett Morejón Trofimova; Daniel Díaz Torres (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Achilles tendon is third most common tendon torn, following the rotator cuff and the quadriceps extensor mechanism. Ruptures can be partial or complete and their etiology is multifactorial. We present the case of a 63-year-old woman who attended the Orthopedics service because of discomfort when walking that had been present for several months and persistent pain in his right heel related to an acetonide triamcinolone injection into the back of the calcaneus. The gap in the tendon (hatchet strike defect) and a Thompson test confirmed the Achilles tendon rupture. The tendon was repaired using a peroneus brevis tendon graft and the repair was reinforced with gastrocnemius aponeurosis. The skin flap necrosis led to conservative debridement, graft exposure, and daily application of a platelet lysate, which was subsequently alternated due to the successful formation of the scar tissue. Epithelialization was reached in the fourth postoperative week. Twelve weeks after surgery, the patient began to resume her normal life. The use of platelet concentrates as adjuvant therapy is rare in these patients. For this reason, we decided to publish this case.